Comprehensive Analysis of Regulatory Networks of m6A Regulators and Reveals Prognosis Biomarkers in Sarcoma - Pang, Boran; Luo, Dinghao; Cao, Bojun; Wu, Wen; Wang, Lei; Hao, Yongqiang (Frontiers in Oncology, 2022)
Sarcomas are rare malignant tumors that may arise from anywhere of the body, such as bone, adipose, muscle and vascular. However, the conventional pathogenesis of sarcomas has not been found. Therefore, there is an urgent need to identify novel therapeutic strategies and improve prognosis effects for sarcomas. Methylation of N6 adenosine (m6A) regulation is a novel proposed regulatory pattern that works in post-transcription level, which was also the most widely distributed methylation modification in eukaryotic mRNA. Growing evidences have demonstrated that m6A modification played an indispensable role in tumorigenesis. Here, we integrated multi-omics data including genetic alterations, gene expression and epigenomics regulation to systematically analysis the regulatory atlas of 21 m6A regulators in sarcoma. Firstly, we investigated the genetic alterations of m6A regulators and found that ~44% TCGA sarcoma patients have genetic mutations. We also investigated the basic annotation of 21 regulators, such as expression correlation and PPI interactions. Then we identified the upstream and downstream regulatory networks of between transcription factors (TFs)/non-coding RNAs and m6A regulators in sarcoma based on motif analysis and gene expression. These results implied that m6A regulator mediated regulatory axes could be used as prognostic biomarkers in sarcoma. Knockdown experiment results revealed that m6A regulators, YTHDF2 and HNRNPA2B1 participated in the cancer cell invasion and metastasis. Moreover, we also found that the expression levels of m6A regulators were related to immune cell infiltration of sarcoma patients.